?Seasonal Variations in the Composition of Essential Oil of Eucalyptus citriodora of Pakistan ? - RAFIQUE, MUHAMMAD; CHAUDHARY, F. M. (Biological Sciences - PJSIR, 1996)
Gas chromatographi examination of the essential oil. The oil was examined on a Pye-Unicam 104 gas chromatograph under the following conditions:-